Discovery of new Gyrase β inhibitors via structure based modeling. (June 2018) - Al-Nadaf, Afaf H.; Salah, Sajeda A.; Taha, Mutasem O.
Graphical abstract: Highlights: 120 Gyrase b inhibitors were collected. LigandFit docking engines has been applied. db-CICA used to identify optimal docking condition. Three pharmacophores were manually constructed and used as 3D query. 12 hits exhibited low micromolar IC50 values. Abstract: Gyrase B is an essential enzyme in the prokaryotes which became an attractive target for antibacterial agents. In our study, we implemented a wide range of docking configurations to dock 120 inhibitors into the in the ATP- binding pocket of Gyrase B enzyme (PDB code: 4GEE ). LigandFit docking engines and six scoring functions were utilized in the study. Furthermore, the ligands were docked in their ionized and unionized forms into the hydrous and anhydrous binding pocket. We used docking-based Comparative Intermolecular Contacts Analysis (db-CICA) which is a novel methodology to validate and identify the optimal docking configurations. Three docking configurations were found to achieve self-consistent db-CICA models. The resulting db-CICA models were used to construct corresponding pharmacophoric models that were used to screen the National Cancer Institute (NCI) list of compounds. In-vitro study represents antibacterial activities for twelve hit molecules with the most active having IC50 of 20.9 μM.